THE BITCOIN STANDARD : The Decentralized Alternative to Central Banking /? - Ammous, Saifedean, 1980-
When a pseudonymous programmer introduced a new electronic cash system that's fully peer-to-peer, with no trusted third party to a small online mailing list in 2008, very few paid attention